Efektivitas Pelayanan Pengaduan Masyarakat Di Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kabupaten Ogan Komering Ilir - Iskandar, Iskandar; Idi, Abdullah; Hakim, Arif Rahman (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2024)
This research aims to evaluate the effectiveness of public complaint services provided by the Investment and Integrated One-Stop Service Agency of Ogan Komering Ilir Regency. The method employed is a qualitative approach with a case study design. Data were collected through interviews, observations, and document analysis. The results indicate that several factors influence the effectiveness of complaint services, such as facility availability, service quality, staff expertise, and procedural clarity. However, there are still obstacles such as limited socialization about the complaint process to the public and a lack of coordination among units within the agency. Therefore, it is recommended that the agency enhance socialization efforts, internal coordination, and service quality to improve the effectiveness of public complaint services.